Modern Arabic sociolinguistics diglossia, variation, codeswitching, attitudes and identity - Albirini, Abdulkafi (Routledge, Taylor & Francis Group, 2016)
Modern Arabic Sociolinguistics outlines and evaluates the major approaches and methods used in Arabic sociolinguistic research with respect to diglossia, codeswitching, language variation and attitudes and social identity. This book analyses the interplay between the various sociolinguistic aspects and examines the complex nature of the Arabic multidialectal, multinational, and multiethnic sociolinguistic situation.